Physical and Chemical Characteristics of Breadfruit (Artocarpus altilis) Seeds Collected from Three Locations in Edo State, Nigeria - Obasuyi, J.O.I.; Nwokoro, S.O. (Pakistan Journal of Nutrition, 2006)
The study was initiated to ascertain some physical and chemical characteristics of the breadfruit seed collected from three locations (Benin City in Oredo, Egor in Egor, and NIFOR in Ovia North-East Local Government Areas) in Edo State, Nigeria. 150 units of well-matured seeded breadfruits were harvested, the fruits were opened and the following physical characters were determined; weight of fruits, number of seeds per fruit, percentage weight of seeds and weight per seed. The seeds after sun-drying (30-35 o C) and seed coat removed were apportioned into two (defatted and undefatted)by extraction followed by proximate chemical analysis (AOAC, 1990).Results indicated that there was no significant (P > 0.05) differences between locations for the physical and chemical characters of the breadfruit and seeds determined. However, it indicated that the mean weight of fruits ranged between 1228.5 and 1291.09 numbers of seeds per fruit (from 73.0 to 77.0) while the mean weight of seeds per fruit and mean weight per seed were between 615.4g and, 750.1g and 8.49g and 9.00g respectively. The seed weights per seed were between 615.4g and 750.1g, 8.49g and 9.00g respectively. The seed weights (percent) per fruit were 50.1, 54.9 and 53.1% for the three locations. The chemical composition of the fruit seed indicated ash to be between 5.02% for Benin and 5.33% for NIFOR and CP, 18.27 (Benin), 19.11 (Egor) and NIFOR, 19.37 percent. Other parameters measured (EE, CF, NFE) were 8.25, 16.18 and 42.10% for Benin City, 8.63, 16.92 and 17.15% for Egor and NIFOR, 8.54, 16.75, and 43.49 percent. Results for the defatted seed meal were (2.75%), CP (27.93%), CF (15.37%) and 48.01% for NIFOR. It may be concluded that locations within the region did not considerably affect the breadfruit and seeds characteristics measured in this study.